Effects of temperature and drought manipulations on seedlings of Scots pine provenances. (26th September 2014) - Taeger, S.; Sparks, T. H.; Menzel, A.; Rennenberg, H.
Abstract Rising temperatures and more frequent and severe climatic extremes as a consequence of climate change are expected to affect growth and distribution of tree species that are adapted to current local conditions. Species distribution models predict a considerable loss of habitats for Pinus sylvestris. These models do not consider possible intraspecific differences in response to drought and warming that could buffer those impacts. We tested 10 European provenances of P. sylvestris, from the southwestern to the central European part of the species distribution, for their response to warming and to drought using a factorial design. In this common‐garden experiment the air surrounding plants was heated directly to prevent excessive soil heating, and drought manipulation, using a rain‐out shelter, permitted almost natural radiation, including high light stress. Plant responses were assessed as changes in phenology, growth increment and biomass allocation. Seedlings of P. sylvestris revealed a plastic response to drought by increased taproot length and root–shoot ratios. Strongest phenotypic plasticity of root growth was found for southwestern provenances, indicating a specific drought adaptation at the cost of overall low growth of aboveground structures even under non‐drought conditions. Warming had a minor effect on growth but advanced phenological development and had a contrasting effect on bud biomass and diameter increment, depending on water availability. The intraspecific variation of P. sylvestris provenances could buffer climate change impacts, although additional factors such as the adaptation to other climatic extremes have to be considered before assisted migration could become a management option.